Inclusive Education Topics Teachers Learned at Teacher Professional Development Programmes: How Did They Benefit? - Kumekpata, Divine Delaedem Kwasi; Ahwireng, Doreen; Boateng, Fred Kofi (Papers in Education and Development, 2024)
This study employed a single case study design involving twenty-two basic schoolteachers from the Ga East Education Directorate in Greater Accra, Ghana. Through interviews, we examined the inclusive education (IE) topics covered in professional development (PD) programmes and the resultant benefits for teachers. The findings demonstrate that IE PD programmes focused on sensitising teachers to IE policies and practices, identifying students with Special Education Needs (SEN), and fostering collaboration among teachers, headteachers, and special education (SPED) coordinators. Notably, participants derive substantial benefits from these programmes, acquiring knowledge on SEN identification, developing a willingness to embrace students with SEN, enhancing teacher agency, and fostering collaborative partnerships among teachers, headteachers, and SPED coordinators to better support students with SEN. The study ' s findings underscore the imperative for comprehensive support from diverse education stakeholders in organising ongoing, practical, and hands-on IE PD programmes for Ghanaian basic schoolteachers. Keywords: Special education needs, inclusive education, professional development, teacher agency, Ghana